Intelligent active force control of a robot arm using fuzzy logic - Mailah, Mailah; Abdul Rahim, Nurul Izzah (IEEE, 2000)

(untitled)
The paper describes a novel and intelligent method of estimating the inertial parameter of a rigid robot arm employing an active force control (AFC) strategy with a fuzzy logic (FL) mechanism embedded in its control loop. The robustness and effectiveness of the proposed central scheme are investigated considering the trajectory track performance of the arm taking into account the application of some forms of external disturbances as the robot describes a reference trajectory given a number of initial and operating conditions. The track performance of the proposed scheme is also compared with an equivalent system employing classical proportional-derivative (PD) control